2018
DOI: 10.7567/jjap.57.06jb03
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling for SiO2 atomic layer deposition for high-aspect-ratio hole patterns

Abstract: A multiscale simulation model is developed for optimizing the parameters of SiO 2 plasma-enhanced atomic layer deposition of high-aspect-ratio hole patterns in three-dimensional (3D) stacked memory. This model takes into account the diffusion of a precursor in a reactor, that in holes, and the adsorption onto the wafer. It is found that the change in the aperture ratio of the holes on the wafer affects the concentration of the precursor near the top of the wafer surface, hence the deposition profile in the hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Comparing experimentally obtained thickness profiles with simulated profiles can provide the initial sticking probability s 0 of the used ALD reactant, as shown for instance by Rose and Bartha 12 and Ylilammi et al 14 Here, s 0 indicates the sticking probability toward the initial surface on which all reaction sites are still available. In several models, e.g., ballistic, 8,31-35 continuum, 14,[36][37][38] and Monte Carlo, 9,10,12,27,30,[39][40][41][42] it is observed that s 0 governs the slope of the leading front of the thickness profile. In this work, the relation between the slope of the profile front and the initial sticking probability has been quantified using the continuum model reported by Yanguas-Gil and Elam 36 to directly determine sticking probabilities from ALD thickness profiles without further modeling.…”
Section: B Simulating Ald Thickness Profiles In 1d Structuresmentioning
confidence: 99%
“…Comparing experimentally obtained thickness profiles with simulated profiles can provide the initial sticking probability s 0 of the used ALD reactant, as shown for instance by Rose and Bartha 12 and Ylilammi et al 14 Here, s 0 indicates the sticking probability toward the initial surface on which all reaction sites are still available. In several models, e.g., ballistic, 8,31-35 continuum, 14,[36][37][38] and Monte Carlo, 9,10,12,27,30,[39][40][41][42] it is observed that s 0 governs the slope of the leading front of the thickness profile. In this work, the relation between the slope of the profile front and the initial sticking probability has been quantified using the continuum model reported by Yanguas-Gil and Elam 36 to directly determine sticking probabilities from ALD thickness profiles without further modeling.…”
Section: B Simulating Ald Thickness Profiles In 1d Structuresmentioning
confidence: 99%
“…For recent 5 years, useful simulation techniques have been adopted to the ALD process. Miyano et al 96 Qu et al 98 developed a detailed SiO 2 -PEALD model with the cycle of SiH 2 ½NHðC 4 H 9 Þ 2 precursor [called bis(tertiary-butylamino)silane (BTBAS)] step and Ar∕O 2 plasma step using a cell removable method. A CCP reactor with a 300 mm diameter and gap length of 1.5 cm was assumed.…”
Section: Ald Modelmentioning
confidence: 99%
“…To understand the ALD coating process on high-aspect-ratio structures and determine the processing conditions needed for conformal coverage, a variety of models have been developed, including analytical/continuum approaches, , kinetic Monte Carlo simulations, , ballistic simulations, and multiscale modeling. A recent review by Cremers et al as well as a book by Yanguas-Gil provide comprehensive overviews of many of these efforts. , Well-defined high-aspect-ratio structures, such as LHAR structures and AAO, are often used to experimentally measure ALD infiltration and assist in the development of diffusion and reaction models. ,, The analytical model by Gordon et al has been used extensively and offered a starting point for numerous other efforts . This model predicts a necessary precursor exposure, defined by the product of the exposure time and precursor partial pressure in the deposition chamber, which is necessary to coat a structure of a specific aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Lankhorst et al. and Miyano et al modeled the transient depletion of the precursor concentration in the reaction chamber in a constant-flow ALD process. , Grillo et al modeled ALD on nanoparticles and micrometer-scale nanoporous particles in a fluidized-bed reactor to optimize precursor utilization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation